Pengaruh Penggunaan Model Pembelajaran Gadget Terhadap Peningkatan Hasil Belajar Matakuliah Zoologi Vertebrata Pada Mahasiswa Program Studi Pendidikan Biologi FKIP Universitas Pattimura - HASAN TUAPUTTY; TRI SANTI KURNIA; RUVIATI SIMAL; RIVALDO MALAWAT (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
Educational paradigm thoughts in this 21st century in line with the development of science and technology. We see nowadays that cellular computation program enables lecturer to record students` assessment data directly from mobile device. Besides, by the use of electronical devices that could be operated to increase and enhance students` learning in various way like enhancing students` understanding in theories, related with a performance or presentation, lab and experiments or written task and assignments. Then mobile device termed gadget. To know the influence of gadget learning model usage towards students` learning result and thinking skill in accomplishing assignments on vertebrate zoology course of college students from biology education faculty of education pattimura university. This research being held in Faculty of Education Pattimura University Biology Education, on Ferbuary 10th - June 10th 2019. Data will be analyzed statistically using SPSS 2.0 Key Words: Gadget Learning Model, Thinking Skill, Students` Learning Result